Factors influencing umbrella fund selection offered by the employee benefits industry in South Africa. - Bapoo, Irshaad (My University, 2016)
This research addresses the factors, which influence an employers or companies decision in umbrella fund selection, which are offered by the employee benefits industry in South Africa. Fuzzy Cognitive Mapping (FCM) was the research methodology utilised as a result of the qualitative and quantitative nature of the study. Nine interviews were carried out with decision makers and industry experts where applicable, based on an initial FCM produced from literature. Thereafter, a reinforced validated FCM was produced which allowed simulations to be run, based on the results from interviews. The research results did not deviate far from the literature with major factors influencing umbrella fund selection being explicit such as administration and servicing, costs, the value add by the employee benefits consultant, the risk benefits provider as well as the investment manager chosen. Furthermore, additional factors such as product marketing, global contractual agreements, industry regulations, decision making bureaucracy as well as the company outlook were identified. This research and its implications are key to providing guidance to employers or companies when selecting products from service providers. Furthermore, the results of this study may allow employee benefits providers to position themselves in such a way so as to take advantage of opportunities within the industry and also to be aware of the potential risks that may arise when developing and marketing products.
MBA Thesis
Keywords: Pension trusts -- South Africa -- Management.